Pertangungjawaban Hukum Pelaku Tindak Pidana Pertambangan Emas Ilegal di Indonesia - Ine Tustinaningsih; Suwari Akhmaddhian (Savana, 2025)
Indonesia is a country with abundant natural resources, including minerals and coal. However, the management of these natural resources faces serious challenges, one of which is the practice of illegal mining, especially unlicensed gold mining which harms the state and pollutes the environment. This research aims to analyze the legal arrangements related to the crime of illegal gold mining in Indonesia and its implementation in the case of Decision Number 16/Pid.Sus/2024/PN Mbo. The method used is normative juridical, by examining legal theory and related legislation. The results showed that Law Number 3 of 2020 concerning Mineral and Coal Mining has clearly regulated illegal mining crimes, including criminal sanctions and heavy fines. However, implementation in the field is still constrained by weak supervision, limited resources, and lack of law enforcement. Case No. 16/Pid.Sus/2024/PN Mbo revealed a violation of Article 158 of the Minerba Law, in which the defendant was found guilty of mining without a license and sentenced to imprisonment and a fine. The conclusion is that legal arrangements related to illegal mining in Indonesia are quite comprehensive, but their implementation requires strengthening. Suggestions include improved coordination between the central government, local governments and communities, as well as stricter law enforcement to effectively address illegal mining.